Allergic Potential and Immunotoxicity Induced by Topical Application of 1-Chloro-4-(Trifluoromethyl)Benzene (PCBTF) in a Murine Model. (14th May 2011) - Franko, Jennifer; Jackson, Laurel G.; Meade, B. Jean; Anderson, Stacey E.
Abstract : The purpose of the studies in this paper was to evaluate the allergic potential, immunotoxicity, and irritancy of the occupationally relevant chemical, 1-chloro-4-(trifluoromethyl)benzene, also known as parachlorobenzotrifluoride (PCBTF), following dermal exposure in a murine model. Evaluation of the sensitization potential, conducted using the local lymph node assay (LLNA) at concentrations ranging from 50% to 100%, identified a dose-dependent increase in lymphocyte proliferation with a calculated EC3 value of 53.1%. While no elevations in total or specific IgE were observed after exposure to any concentration of the chemical, significant increases in IFN-γ protein production by stimulated draining lymphoid cells were observed, indicating a T-cell-mediated response. Dermal exposure to PCBTF was not found to alter the immune response to a T-cell-dependant antigen. These results demonstrate that PCBTF has the potential to induce allergic sensitization following dermal exposure and based on LLNA results would be classified as a weak sensitizer.